Biomechanical studies on the interrelation between trunk muscle strength and sports performance - Gerber, M.; Faude, O.; Hanssen, H.; Gruber, M. (Universität Basel, Faculty of Medicine, Departement Sport, Bewegung und Gesundheit, Bereich Sportwissenschaft, Sport und psychosoziale Gesundheit, 2020)
In team sports such as football, ice hockey or basketball, athletes benefit from the body`s ability to tolerate high loads during start and stop movements, changes of direction, and tackles during competition. Likewise, in individual sports, such as track-and field or cross-country skiing, maximum performance is only possible with optimally trained and optimally controlled muscles. The strength of the abdominal and back muscles is widely considered crucial, as it is responsible for a high stability of the trunk during movement. The stability of the trunk is not only considered the basis of a high performance in specific sports discipline, but can also contribute to reduced back pain and risk of injuries to the lower extremities and, in general, to fewer overuse injuries. Therefore, a considerable amount of time in training is devoted in order to improve trunk strength in sports. A considerable number of tests, then, is typically applied in order to evaluate trunk muscle strength in athletes. But, surprisingly, the relevance and comparability of the measured values are poorly understood. Therefore, this study on some central aspects of the interrelation of trunk muscle strength and sports performance sets out to highlight the contribution made to the improvement of the athletes' performance in a wide range of sports and to the prevention of sports injuries. This thesis seeks to critically access the methodological presumptions which underlie and have guided the existing scholarship, and the experimental research, on the role of trunk muscles in sports. It will do so by using different methodological perspectives in its discussion and by making use of a set of new investigations and tests. In particular, the quantification of the activity of the trunk muscles in different movements will be discussed as well as measurements which try to determine the strength of the trunk muscles. Finally, this study aspires to contribute to a better overall understanding of the interrelation of trunk muscle strength and athletic performance on the one hand and to preventive training on the other hand. In four studies presented in this thesis, different methodological approaches are used to that end: electromyographic measurements for the determination and analysis of muscle activation as well as different methods of strength assessment for the differentiation of various strength qualities. The differentiation of the strength qualities allows the description of various aspects of trunk strength, such as maximum strength and strength endurance, which relate to essential athletic performance parameters such as sprint, change of direction or balance. The performance in the strength of the abdominal and back muscles is measured with laboratory and field methods in different movements. The findings are not only used to re-address the discussions on the comparability and reliability of different measuring methods but also seek to advance our understanding of the degree of activity of trunk muscles and the influence of trunk strength on basic performance parameters in sport. In the first study, a field test method which is frequently used in Switzerland (Bourbon test: prone plank, side plank, Sorensen test) is compared with a laboratory procedure (isometric trunk flexion, extension, lateral flexion, rotation test) in a group of high-level soccer players. This study aims to compare different assessment methods. No relevant correlation between the performance in the field test (time to failure) and the maximum isometric force measurements (Pearson's correlation: -.14< r <.36) is observed. The maximum force output, therefore, does not indicate the strength endurance performance and vice versa. The performances in the field measurements do not differ between men and women. Muscle activity during strength endurance performance, however, is very high and exceeds 100% of maximum voluntary isometric muscle activation. This effect is more pronounced among female athletes than males. All strength endurance tests show a continuous increase in abdominal muscle activity over time, indicating muscular fatigue. However, in the prone plank and side plank test the upper extremities are mentioned as the main reason for the test termination, whereas in the Sørensen test it is the trunk. The prone plank test is frequently used in sports to assess trunk strength but, as the discussion of the results demonstrate, the validity of the test to determine trunk strength should be questioned. However, the high activation of the muscles involved, especially in the second half of the maximum performance time, justifies the use of the exercises in strengthening programs for the trunk muscles. In the second study, the reliability for different movement directions of the trunk was investigated on an isokinetic force measuring device (IsoMed 2000). Fifteen healthy sports students were tested in an isometric and isokinetic mode (movement speed 60°/s and 150°/s) for the movement directions trunk flexion and extension, as well as right and left rotation. Maximum trunk strength was evaluated during five test days, including a familiarization test. The most reliable test mode was the isokinetic force measurement of trunk flexion and extension at a speed of 60° per second (ICC=0.92-0.96; 3.7% < CoV < 7.7%; 0.08 Nm/kg < SEM < 0.24 Nm/kg). The reliability of the isometric and isokinetic strength measurement at 150°/s as well as the other directions of motion can also be described as sufficient. However, familiarization tests should always be performed as the reliability between the familiarization measurement and the first day of measurement was lower than between the other four tests. In the third study, the relevance of trunk muscle strength for athletic performance was investigated in a three-armed randomized controlled cross-over study with 24 sports students in which parameters such as a linear sprint, agility and balance were evaluated. A fatiguing 20-minutes workout aiming either to fatigue leg or trunk muscles or for control condition 20 min of rest were performed. Before and after the fatigue protocol or control condition, sprint, agility, and balance performance as well as leg and trunk muscle strength were assessed. The fatigue protocol resulted in fatigue of the respective body region. Trunk muscle fatigue resulted in a decrease in change of direction sprint and balance performance but had no affect linear sprint speed. Leg fatigue impaired, except for trunk strength, all performance parameters to a greater extent in comparison to trunk fatigue. Thus, trunk muscle strength can be regarded as relevant for selected physical performance components. Consequently, training of the trunk muscles can be recommended in sports where the speed of directional changes and balance are relevant. However, the importance of leg strength for sports performance can be rated higher. Finally, the fourth study investigated the activation of trunk muscles as well as the deformation of the lumbar spine during a popular strength exercise such as barbell squats (back squat, front squat, overhead squat). Two standing conditions were defined (I) one with both feet on the ground and (II) one with a reduced base of support standing only on the forefoot without ground contact of the heels. Since the abdominal muscles are considered responsible for controlling the lordosis in the lumbar spine, the lordosis movement was also tracked. For this purpose, a marker-based, three-dimensional motion analysis system (Qualysis, visual3D) and force plates were used to record the different squat variations. Based on joint angles and body markers, the squat movement was divided into three segments (a lowering, turning, raising phase) and the electromyographic data of the trunk muscles and the sway path of the center of pressure on the force plate were analyzed. While the activity of the trunk muscles differed between squat types, there was no relevant effect of the standing condition on muscle activity. To sum up, the findings of this thesis seek to contribute to a better understanding of the relevance and function of trunk muscle strength in athletic performance. The results presented here provide relevant findings for recreational and competitive sports and strengthen the conclusion that trunk muscle strength substantially affects athletic performance. Therefore, the application of tests to determine trunk strength, is reasonable in various settings. However, the validity of the prone plank test which is frequently applied in sports practice must be questioned, since it is usually terminated due to fatigue of the upper extremities and not due to fatigue of the trunk muscles. The use of alternative measurement methods to determine trunk strength therefore is recommended here. Isokinetic trunk strength assessment is a reliable laboratory test procedure. Various training interventions are frequently recommended in order to improve trunk strength, often involving squatting exercises. The variation of the squat type caused more considerable differences in trunk muscle activity compared to a reduction in the base of support. Therefore, variations of barbell squats could be promising alternatives in the engagement of trunk muscles. Trunk strength training can be an essential supplement in strength training. Overall, however, the contribution of leg muscles to athletic sprint and balance performance can be considered more relevant.